Povezanost dinamike gibanja z uspešnostjo plesalcev pri latinsko-ameriškem plesu samba - Premelč, Jerneja (Šport (Ljubljana), 2017)
The aim of the study was to investigate the movement dynamics in samba in terms of time and speed of movement in the static and dynamic phases, using different quality groups. The sample consisted of 48 senior-team dance couples who were divided into three quality groups based on their ranking at the 2012 Slovenia Open international dance competition. The dancers danced the major part of the choreography (72.8%) in the static phase. The average speed of dancers' movement in the static phase was 0.72+-0.1 m/s and in the dynamic one 1.42+-0.2 m/s. There were no statistically significant differences between the quality groups, however, better dancers moved faster in the static phase and slower in the dynamic phase, their individual phases were shorter and the number of passages from one phase to another higher. These characteristics of the movement dynamics of highperforming dancers can also be used as guidelines for coaches and dancers when composing samba choreography.
Keywords: dinamika gibanja; movement dynamics; ples; samba; sport; sport dance; šport; športni ples